Infrastructure enhancement and households’ economic activities: lesson from Indonesia - Dwi Wuilandari; Narmaditya, Bagus Shandy; Prayitno, Putra Hilmi; Ishak, Suryati (Sciedu Press, 2019)
This study aims at examining the impact of infrastructure advancement of Southern Cross Lane (JLS) in Malang, Indonesia toward households’ economic activities. Furthermore, this study intended to understand the presence of new road infrastructure and tourism sectors toward households’ economic activities. This research applied a descriptive study by conducting fo cus group discussions with stakeholders and the local community in Malang, Indonesia. In addition, semi structured questionnaires were implemented to obtain a better understanding of the existing phenomenon. The findings of the study showed that in the sho rt term, the presence of a new road in Southern Cross Lane changes the economic activities of the household while in the long term, it provides various opportunities to be developed such as tourism sectors, hotels, and restaurants. However, the development efforts from each region depend on the plan of the local community. Furthermore, the existence of a new road in Southern Cross Lane contributes to greater access between cities in the south of East Java in Indonesia.